Profil Empati Multibudaya Masyarakat Desa Wisata Cibuntu - Fahira, Amartya Alka; Nurwulan, Anisa; Cahya, Arinnisa; Zahra, Kaila Aulia; Putri, Kharisma Amelia; Rahmani, Sabrina Tiara Putri; Supriatna, Mamat (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
The Cibuntu Tourism Village community faces challenges in maintaining social harmony amidst intense cross-cultural interactions due to increased tourist visits from various backgrounds. This study aims to identify the multicultural empathy profile of the Cibuntu Tourism Village community and formulate effective strategies in creating harmonious cross-cultural relationships. The research approach used a field study method in the form of interviews with managers, local communities, and children of Cibuntu Tourism Village, as well as strengthening the theory through literature review. Data analysis was conducted systematically to explore the pattern of community empathy in preserving traditions, welcoming visitors, and building solidarity between citizens. The results showed that the Cibuntu Tourism Village community has a high level of empathy, as seen from efforts to preserve traditions such as Sedekah Bumi, hospitality towards visitors, and solidarity in helping others. This inclusive attitude not only strengthens local social relations but also creates a positive image of the village in the eyes of tourists. The findings confirm the importance of multicultural empathy as the foundation of harmonious and inclusive sustainable tourism development.